DETERMINATION OF ANTHROPOGENIC CHANGES ON THE URBANIZED TERRITORIES BY FACILITIES OF GIS - Patrakeyev, Igor; Ziborov, Victor; Lazorenko-Hevel, Nadia (GeoScience Engineering, 2017)
A research aim is a receipt of cartographic model of the urbanized territory by means of thermal survey in an infrared range. Further possibility to reduce those zones on the urbanized territories that differ in the level of superficial heat appears by means of this cartographic model. And also we will be able to reduce proof thermal anomalies and thermal structures localities that is related to the natural and anthropogenic systems. On the examples of cities of Ukraine Enerhodar and Nikopol we defined sources of caloradiances from major industrial concerns, and also from thermal and nuclear power plant. For comparison we built the model of thermal structure of city Tokai and nuclear power plant with the of the same name Tokai (Japan). The sources of caloradiances can be, for example, pipes of thermal power station, ponds-coolers, corps of steel-making productions and other similar objects. If the sizes of such source are known, then we will be able to get the absolute values of temperatures.